2020
DOI: 10.1002/iub.2414
|View full text |Cite
|
Sign up to set email alerts
|

ATF4‐modified serum exosomes derived from osteoarthritic mice inhibit osteoarthritis by inducing autophagy

Abstract: Activating transcription factor 4 (ATF4) is critical for chondrocyte proliferation and bone formation. Exosomes are considered as promising gene-delivery vehicles for the treatment of osteoarthritis (OA). This study utilized the serum-derived exosomes from OA mice as the gene-delivery vehicles for ATF4 gene therapy and explored their therapeutic effects on OA. Meniscus injury-induced OA model was established by the excision of anterior part of medial meniscus in the right knee of C57BL/6J mice. Exosomes were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Activated transcription factor 4 (ATF4) is essential for chondrocyte proliferation and bone formation. Wang et al introduced ATF4 mRNA into serum-derived EVs from OA mice (OA-EVs) by electroporation, and found ATF4-modified OA-EVs can protect cartilage and alleviate OA progression by inducing autophagy [ 60 ].…”
Section: Cell Pretreatment Strategymentioning
confidence: 99%
“…Activated transcription factor 4 (ATF4) is essential for chondrocyte proliferation and bone formation. Wang et al introduced ATF4 mRNA into serum-derived EVs from OA mice (OA-EVs) by electroporation, and found ATF4-modified OA-EVs can protect cartilage and alleviate OA progression by inducing autophagy [ 60 ].…”
Section: Cell Pretreatment Strategymentioning
confidence: 99%
“… 101 Valadi et al 102 were the first to discover the presence of mRNAs and miRNAs in exosomes, and indicated that exosomes could modify the protein production and gene expression of target cells by transferring exosomal mRNAs or miRNAs. Wang et al 80 investigated the therapeutic effect of the activating transcription factor 4 ( ATF4 ) gene in cartilage regeneration by introducing ATF4 mRNA into exosomes via electroporation. The effects of exosomes derived from OA serum (OA-Exos) and ATF4 mRNA-overexpressing exosomes (ATF4-OA-Exos) were compared, and showed that the ATF4-OA-Exos were more potent compared to the OA-Exos in preventing and alleviating cartilage degeneration via the stimulation of autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, it remains unclear if multiple injections are more effective compared to single injection for promoting cartilage regeneration, as none of the studies compared the therapeutic effect of single and multiple injections. Cosenza et al 74 and Wang et al 80 showed that the effect of exosomes from a single intra-articular injection may be month-long. This is most probably due to the direct exosome administration to the target site (cartilage is avascular and alymphatic; thus, the clearance of the injected exosomes is slower) and the exosomes might induce cellular reprogramming and remodel resident or injured cells by activating regenerative mechanisms by transferring bioactive molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ATF4-OA-Exosomes promote the autophagy and inhibit the apoptosis in TNF-α or tunicamycin treated chondrocytes (Wang Y. et al, 2021).…”
Section: Exosomes Derived From Primary Chondrocytesmentioning
confidence: 94%